2001
DOI: 10.1177/107155760100800310
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E mRNA Overexpression in Epithelial Ovarian Cancers: Inverse Correlation with p53 Protein Accumulation

Abstract: Cyclin E mRNA overexpression frequently occurs in ovarian cancers without p53 protein accumulation. Cyclin E might have an important effect on the development of a limited number of ovarian cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In particular, CCNE1 was shown amplified by FISH analysis in different tumor types including EOCs (Schraml et al, 2003). The overexpression of CCNE1 was observed at the mRNA (30%) and protein (43%) level in ovarian tumors compared to normal ovaries (Sawasaki et al, 2001) and was also associated with a poor prognosis (Rosenberg et al, 2001;Sui et al, 2001a;Farley et al, 2003;Milde-Langosch et al, 2003;Schraml et al, 2003). Moreover, a gradation in CCNE1 expression from benign to LMPs (50%) and to TOVs (70%) has also been reported (Sui et al, 2001a).…”
Section: Discussionmentioning
confidence: 97%
“…In particular, CCNE1 was shown amplified by FISH analysis in different tumor types including EOCs (Schraml et al, 2003). The overexpression of CCNE1 was observed at the mRNA (30%) and protein (43%) level in ovarian tumors compared to normal ovaries (Sawasaki et al, 2001) and was also associated with a poor prognosis (Rosenberg et al, 2001;Sui et al, 2001a;Farley et al, 2003;Milde-Langosch et al, 2003;Schraml et al, 2003). Moreover, a gradation in CCNE1 expression from benign to LMPs (50%) and to TOVs (70%) has also been reported (Sui et al, 2001a).…”
Section: Discussionmentioning
confidence: 97%
“…Cyclin E (Ccne1) is required for the G1--S phase and has been reported to be over-expressed in many types of cancer. CCNE1 was shown to be over-expressed both at the mRNA and protein level in ovarian tumors compared to normal ovaries 37 and was also associated with a poor prognosis. [19][20][21][22] These results are consistent with those seen in our analysis where Ccne1 represents the most specific marker for distinguishing noninvasive from invasive tumors and it also correlates with the stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we have shown that in both normal and tumor cells, at the level of RNA, cyclin E is present as multiple splice variants; however, these splice variants do not give rise to protein products (16). Therefore, it seems that the primary process that contributes to deregulation of cyclin E is through posttranslational proteolytic cleavage of the full-length protein by elastase, which results in generation of the low molecular weight (LMW) forms (17).In ovarian cancer, cyclin E gene amplification has been described in 12% to 21% of ovarian tumors (7, 18) with RNA overexpression reported in as many as 30% of cases (7,18,19) and up to 70% of tumors are reported to show overexpression at the protein level (20,21). Of note, all the studies of cyclin E protein expression have relied on immunohistochemical techniques that may not be as sensitive as Western blot analysis for the overexpression and detection of the LMW form of this cell cycle regulator (12).…”
mentioning
confidence: 99%
“…In ovarian cancer, cyclin E gene amplification has been described in 12% to 21% of ovarian tumors (7, 18) with RNA overexpression reported in as many as 30% of cases (7,18,19) and up to 70% of tumors are reported to show overexpression at the protein level (20,21). Of note, all the studies of cyclin E protein expression have relied on immunohistochemical techniques that may not be as sensitive as Western blot analysis for the overexpression and detection of the LMW form of this cell cycle regulator (12).…”
mentioning
confidence: 99%